Pengaruh Intensitas Penggunaan Media Sosial terhadap Tingkat Kecemasan Sosial Generasi Z di SMA Negeri 2 Palangka Raya - Cindy Yemima Sihombing; Munika Munika; Septia Yuspita (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2026)
The increasing use of social media among teenagers can lead to dependency when digital activities become a major part of their daily lives. This condition may affect teenagers' psychological well-being, one of which is social anxiety that can interfere with their interactions with others. The aims of this study is to examine the effect of social media use intensity on the social anxiety levels of Generation Z students at SMA Negeri 2 Palangka Raya, identify students' social anxiety levels, and analyze their intensity of social media use. Quantitative method with a descriptive approach is used in this study. The respondents were 30 students from SMA Negeri 2 Palangka Raya selected through simple random sampling. By distributing questionnaires directly to the respondents, data were collected and analyzed using univariate analysis to determine the frequency distribution also percentage of each variable. The results presented that students' social media use intensity was relatively high. This was indicated by 56.7% of respondents strongly agreeing that they use social media every day, while 50.0% spent around 3–5 hours per day on social media. The findings also showed a tendency toward social anxiety, with 60.0% of respondents agreeing that they were afraid of receiving negative judgments from others. However, most students were still able to interact in social situations, as shown by 70.0% of respondents reporting positive social interactions.